2019
DOI: 10.3758/s13420-019-00392-7
|View full text |Cite
|
Sign up to set email alerts
|

Reversal training facilitates acquisition of new learning in a Morris water maze

Abstract: Two experiments determined the effect of interference training on subsequent spatial learning in a Morris water maze. Rats first learned that a platform was located in a quadrant marked by landmarks A and B. Different groups of rats either continued or reversed that training. In the reversal condition the platform was opposite to the initially trained quadrant. On test, a new cue, C, was added and the platform was located in the new AC quadrant. Rats that had received the reversal training learned the location… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…This interpretation agrees with the idea that the ambiguity that extinction produces in the organism would lead to a general increase in attention (e.g., Schmajuk et al, 1996) through the engagement of the attentional exploratory mechanism (Le Pelley et al, 2016) in a search for the elements that allow the organism to solve the uncertainty that the ambiguous situation produces. According to these interpretations, the context-switch effect could be considered like a side effect of a wider phenomenon that, under an ambiguity situation, facilitates subsequent learning about contexts, as shown in this experimental series, but also about different tasks and procedures that were not part of the original learning, such as it has been recently reported in the literature (Alcalá et al, 2019; Alcalá et al, 2020; González et al, 2019; see also Rosas & Nelson, 2019).…”
Section: Discussionsupporting
confidence: 59%
“…This interpretation agrees with the idea that the ambiguity that extinction produces in the organism would lead to a general increase in attention (e.g., Schmajuk et al, 1996) through the engagement of the attentional exploratory mechanism (Le Pelley et al, 2016) in a search for the elements that allow the organism to solve the uncertainty that the ambiguous situation produces. According to these interpretations, the context-switch effect could be considered like a side effect of a wider phenomenon that, under an ambiguity situation, facilitates subsequent learning about contexts, as shown in this experimental series, but also about different tasks and procedures that were not part of the original learning, such as it has been recently reported in the literature (Alcalá et al, 2019; Alcalá et al, 2020; González et al, 2019; see also Rosas & Nelson, 2019).…”
Section: Discussionsupporting
confidence: 59%
“…Similarly, Liberman (1951) showed that extinction of one response (runway running or lever pressing) facilitated the acquisition of the other. Recently, we have shown that a discrimination reversal in a water maze facilitated learning a new, third, platform location (Alcalá, Callejas-Aguilera, Nelson, & Rosas, 2019). A variety of results suggest that ambiguity produced by extinction or some other interference treatment arouses attention more generally, not simply to contexts.…”
mentioning
confidence: 98%
“…In rats, Shanab and Cotton (1970) found that extinction of runway running facilitated a subsequently learned T-maze discrimination. Alcalá, Callejas-Aguilera, Nelson, and Rosas (2019) found that rats that had an interference experience learned faster about the new location of a hidden platform in a water maze. De la Casa, Mena, Ruiz-Salas, Quintero, and Papini (2018) found that the experience of reward devaluation attenuated subsequent latent inhibition in a fear conditioning paradigm.…”
mentioning
confidence: 99%
“…This seems to be the case in the studies summarized within the previous paragraph. Unfortunately, most of the studies that report facilitation of new learning after interference compared a group that received the interference treatment with a group that received simple training, rather than with a naïve group (Alcalá et al, 2019; De la Casa et al, 2018; González et al, 2019; Nelson et al, 2018). This design feature allows for an explanation of the results in terms of attenuation of the retardation of learning that otherwise would appear as a consequence of the previous experience of acquisition, rather than in terms of uncertainty facilitating subsequent learning.…”
mentioning
confidence: 99%